Supercharacters and Superclasses of Certain Abelian Groups - Hadiseh Saydi; Mohammad Reza Darefsheh; Ali Iranmanesh (IndoMS, 2022)
‎Supercharacter theory is developed by P‎. ‎Diaconis and I‎. ‎M‎. ‎Isaacs as a natural generalization of the classical ordinary character theory‎. ‎Some classical sums of number theory appear as supercharacters which are obtained by the action of certain subgroups of GL_d(Z_n) on Z_n^d‎. ‎In this paper we take Z_p^d‎, ‎p prime‎, ‎and by the action of certain subgroups of GL_d(Z_p) we find supercharacter table of Z_p^d‎.